1989
DOI: 10.1042/bj2600789
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a labile rat glutathione transferase of the Mu class

Abstract: A labile GSH transferase homodimer termed 11-11 was purified from rat testis by GSH-agarose affinity chromatography followed by anion-exchange f.p.l.c. The enzyme is unstable in the absence of thiol(s) and has relatively low affinity for both 1-chloro-2,4-dinitrobenzene (Km 4.4 mM) and GSH (Km(app.) 4.4mM). Its mobility on SDS/polyacrylamide-gel electrophoresis is slightly less than that of subunits 3 and 4 and its pI is 5.2. Subunit 11 has a blocked N-terminal amino acid residue, but after CNBr cleavage fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…Hepatocytes were treated with ␣-amanitin (2 g/ml) in the absence or presence of 100 units/ml IL-1. Total RNA isolated from cells 0, 4,8,12,14,16,18,20,24, and 28 h following ␣-amanitin treatment were analyzed by Northern blot and hybridized with the rGSTM1 probe as described under "Experimental Procedures." rGSTM1 mRNA level was related to 18 S rRNA levels, and values are represented as the log of the untreated controls.…”
Section: Figmentioning
confidence: 99%
“…Hepatocytes were treated with ␣-amanitin (2 g/ml) in the absence or presence of 100 units/ml IL-1. Total RNA isolated from cells 0, 4,8,12,14,16,18,20,24, and 28 h following ␣-amanitin treatment were analyzed by Northern blot and hybridized with the rGSTM1 probe as described under "Experimental Procedures." rGSTM1 mRNA level was related to 18 S rRNA levels, and values are represented as the log of the untreated controls.…”
Section: Figmentioning
confidence: 99%
“…3B). Cyanogen bromide cleavage of GST11-11 (Yo or rG-STM5) (17) yielded an identical sequence between the putative CNBr cleavage site methionine residues of this particular peptide 9, and Hsieh et al (22) recently found this peptide after protease digestion of a rat testicular GST. Those authors were apparently unaware that the N-terminal sequence of this subunit extends beyond that of other Mu-class subunits and assumed that this peptide was near the N terminus of the GST with the first methionine at position 2.…”
Section: Iodo[mentioning
confidence: 99%
“…Indeed, this study establishes that a labile and poorly characterized rat subunit previously designated as Yo or GST 11 (14,16,17) and mouse mGSTM5 are similar to the human hGSTM3 subunit in terms of structure, catalytic mechanisms, tissueselective expression patterns, and other unique properties.…”
mentioning
confidence: 99%
“…PB was dissolved in phosthey are not required to be accepted pharmaceuticals. phate 21 Tissues or cells were treated with MC (20 mg/kg/day intraperitoneally, inwere homogenized in buffer A (150 mmol/L of KCl, 50 mmol/ jected in corn oil [2 mL/kg] for 3 or 5 days) 9 or with OPZ, L of phenylmethanesulfonyl fluoride, 1 mmol/L of ethylenediwhich was incorporated into the diet at a final concentration aminetetraacetic acid, and 2 mmol/L of dithiothreitol in 10 of 0.075% (wt/wt) for 3 or 5 days. 10 Four animals were used mmol/L of potassium phosphate buffer, pH 7.0), and the sufor each experimental condition and were killed 24 hours pernatant cytosol fraction was recovered.…”
mentioning
confidence: 99%